PENGARUH PEMAKAIAN KOMBINASI MINYAK JINTEN HITAM (Nigella sativa) dan MADU (Apis mellifera) SEBAGAI ANTI-ACNE SECARA TOPIKAL PADA SUKARELAWAN WANITA - Anjani, Baiq Lenysia Puspita; Hati, Ari Sabar; Az-Zahra, Halimah; Rahmawanti, Fitri; Darmawan, Endang (Pharmaciana, 2015)
Acne mostly affects teenagers with prevalence of 85%. Changing habits of cosmetics may affect the incidence of acne vulgaris. Healing acne can use herbal ingredients such as black cumin oil and honey. Black cumin oil effective for treating mild acne vulgaris and moderate acne vulgaris. Honey has property that can kill the bacteria Propionibacterium acnes. Â The purpose of this study is to determine the anti-acne activity in use of black cumin oil and honey combination in 1:1 ratio for 14 days in women. This study included experimental study with pre-post treatment study design. There are 2 groups, control group (six women volunteer) and treatment group (six women volunteer). For 14 days, control group use chemical drugs anti-acne, while treatment group use black cumin oil and honey combination in 1:1 ratio. Analysis of data used independent sample t-test with confidence interval 95%. The results show that treatment group of women who use black cumin oil and honey combination in 1:1 ratio for 14 days compared with the control group of women there is no difference in reducing the number of parameters black blackheads, white blackheads, papules, pustules, hyperpigmentation, erythema, pruritis, xerosis, desquamation, and sunburn with a value of p> 0.05. The conclusion of this study is the use black cumin oil and honey combination in 1:1 ratio for 14 days has effect as Â anti-acne in women, but statistically not significant.Â